FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN PENGHUNI APARTEMEN TAMANSARI PROSPERO SIDOARJO - Susilowati, Sri; Farida, Ilya; Budiarti, Wiwik (Lembaga Penelitian Dan Pengabdian Kepada Masyarakat Universitas 17 Agustus 1945 Surabaya, 2019)
This study aims to analyze the effect of service quality simultaneously and partially on satisfaction of residents of Tamansari Prospero Sidoarjo Apartments and to find out the dominant influential variables. This study uses primary data from questionnaires with 110 respondents. Measurements using a Likert scale and processed statistically using the formula of multiple linear regression with SPSS version 21 program, namely the F test and t test at a significant level Î± (0.05). F Test Results proved correct, Physical Evidence (X1), Reliability (X2), Responsiveness (X3), Assurance (X4) and Attention (X5) simultaneously had a significant effect on the satisfaction of Apartment residents. The t-test results proved correct, physical evidence (X1), responsiveness (X3) and attention (X5) partially had a significant effect. Whereas Reliability (X2) and Guarantees (X4) proved partially no significant effect. Proved to be true Physical evidence (X1) has a dominant influence on the satisfaction of residents of Tamansari Prospero Sidoarjo Apartments